Much more than a checklist: An introduction to the birds and nature of Cyprus (Avocetta, 2025)
Review of Flint P. & Richardson C., 2024. The Birds of Cyprus. An annotated Checklist. BOC Checklist Series: 28. British Ornithologists’ Club. Tring, UK, 492 pp.